2020
DOI: 10.1111/pde.14398
|View full text |Cite
|
Sign up to set email alerts
|

Disseminated cutaneous tuberculosis from BCG vaccination site in an immunocompetent child

Abstract: A healthy 4-month-old girl presented with widespread scaly papules and a nodule over the site of BCG immunization. A diagnosis of disseminated cutaneous tuberculosis in an immunocompetent child was confirmed with biopsy. The child was treated with antituberculosis therapy without recurrence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 3 publications
0
5
0
Order By: Relevance
“…The possibility of disseminated mycobacterial infection secondary to BCG vaccination has also been observed. According to a case study by Dhar et al, the administration of the BCG vaccine first started as a local swelling of the injection site, which then resulted in the disseminated mycobacterial infection in an immunocompetent child [ 17 ]. Dhar notes the rarity of the dissemination of mycobacteria from the BCG vaccine because local cutaneous complications, along with other CTBs such as lupus vulgaris, tuberculids, and even leprosy, are not uncommon [ 1 ].…”
Section: Incidence and Epidemiology Of Tb And Cutaneous Tbmentioning
confidence: 99%
See 2 more Smart Citations
“…The possibility of disseminated mycobacterial infection secondary to BCG vaccination has also been observed. According to a case study by Dhar et al, the administration of the BCG vaccine first started as a local swelling of the injection site, which then resulted in the disseminated mycobacterial infection in an immunocompetent child [ 17 ]. Dhar notes the rarity of the dissemination of mycobacteria from the BCG vaccine because local cutaneous complications, along with other CTBs such as lupus vulgaris, tuberculids, and even leprosy, are not uncommon [ 1 ].…”
Section: Incidence and Epidemiology Of Tb And Cutaneous Tbmentioning
confidence: 99%
“…Even rarer, a tuberculous chancre can form with inoculation of M. bovis to the skin after local trauma, and this accounts for about 1–2% of CTB [ 52 ]. Multiple reports have been published describing the extremely rare development of a CTB reaction after the administration of the BCG vaccination [ 17 ]. Dhar et al describe a previously healthy 4-month-old diagnosed with biopsy-confirmed disseminated CTB at the site of BCG immunization that resolved without recurrence after anti-TB treatment [ 17 ].…”
Section: Clinical Presentation Of Ctbmentioning
confidence: 99%
See 1 more Smart Citation
“…Disseminated cutaneous tuberculosis is rarely reported both in immunosuppressed and immunocompetent children receiving the vaccine at birth [ 21 ].…”
Section: Mycobacterial Skin Infectionsmentioning
confidence: 99%
“…Rarely, disseminated CTB can result from the BCG vaccine in immunocompetent individuals. 47 These lesions present with widespread papules over the site of the BCG immunization. Anti-tubercular treatment for 6 months has been sufficient in previous cases.…”
Section: Introductionmentioning
confidence: 99%